Pengaruh Penambahan Kalsium Karbonat Sebagai Fortifikan Kalsium Terhadap Sifat Fisikokimia dan Organoleptik Permen Jeli Susu - Netty Kusumawati, Sherly Novita Lesmana, Thomas Indarto Putut S., (Jurnal Teknologi Pangan dan Gizi, 2008)
Jelly candy is a candy consist of sucrose, glucose, acid and gel performing material with a texture and certain elasticity. Calcium fortification will become added value on the product. Calcium needed on the bone performing and to prevent the osteoporosis. Protein and vitamin D contain from milk in milk jelly candy will increace the absorption of calcium on the body. The calcium carbonate adding will affect on jelly candy pH. pH will affect on the jelly performing which it can affect texture. Calcium can bound with protein perform calcium bridge which is strenghten texture. Unsolved of calcium will produce â€œchalky mouthfeelâ€, gritty in the mount and opaque appearance. This study will examine the effect of the difference of the adding calcium carbonate toward physic, chemical and sensory characteristic on the milk jelly candy and can be accepted by consumers. Milk jelly candy contain calcium which it made from gelatin mix, sucrose, glucose syrup, water, full cream powder milk and calcium carbonate. This study had done by the making of the milk jelly candy with variation on the adding of calcium carbonate. The study design were used is Group Randomized Design with single factor contain one factor: 4 level of calcium carbonate concentration (0,77%; 1,53%;2,30%;3,06%) with 6 replication. The examination including physical characteristic (texture, color), chemical characteristic (water content, pH, calcium content) and organoleptics (texture, taste, mouthfeel, colour). Organoleptics test using Completely Randomized Design contain 4 level of calcium carbonate concentration (0,77%; 1,53%;2,30%;3,06%) with 80 panelis. The obtained data came from the observation results then had been analyzed statistically by NOVA test Î±=5%. If the ANOVA shows the difference, then would be continued by Duncan Multiple Range Test. The best optional with weighing test. The parameter have been choose for the weighing test is organoleptics (texture, taste, mouthfeel, color). The result shows that different level of calcium carbonate gave significant differences of moisture content, pH, elasticity, compresibility, brightness, hedonic range of colour, taste, texture milk jelly candy, but did not gave significant differences of hedonic range of mouthfeel. The higher level of calcium carbonate, decreased moisture content of milk jelly candy, while pH, elsticity, compresibility, brightness were increase. The best fortification level of milk jelly candy was 3,06%, which gave hedonic score (organoleptics) of colour 5,77; taste 5,20; texture 5,20; mouthfeel 5,18; moisture content 15,85%, pH 7,80, compresibility 270,58 N/20mm, elasticity 4,92 N/50mm, brightness 59,15, calsium level 1,22%.